2020
DOI: 10.1101/2020.06.07.139030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EXOC1 regulates cell morphology of spermatogonia and spermatocytes in mice

Abstract: 31Spermatogenesis requires high regulation of germ cell morphology. The 32 spermatogonia regulates its differentiation state by its own migration. The male 33 germ cells differentiate and mature with the formation of syncytia, failure of 34 forming the appropriate syncytia results in the arrest of spermatogenesis at the 35 spermatocyte stage. However, the detailed molecular mechanisms of male germ 36 cell morphological regulation are unknown. Here, we found that EXOC1 is 37 important for the pseudopod formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…S14c,d). Furthermore, we generated KO mice for the Stx2 gene using the two-cut strategy to cleave 727 bp, including exon 5 of Stx2 (42). DAJIN reported that 13 of the 29 founder mice (BC01, BC03, BC04, BC05, BC07, BC09, BC14, BC15, BC20, BC21, BC22, BC23, and BC24) had the 'Mutated Del' allele (Additional file 2: Fig.…”
Section: Dajin Identifies Knockout Allelesmentioning
confidence: 99%
“…S14c,d). Furthermore, we generated KO mice for the Stx2 gene using the two-cut strategy to cleave 727 bp, including exon 5 of Stx2 (42). DAJIN reported that 13 of the 29 founder mice (BC01, BC03, BC04, BC05, BC07, BC09, BC14, BC15, BC20, BC21, BC22, BC23, and BC24) had the 'Mutated Del' allele (Additional file 2: Fig.…”
Section: Dajin Identifies Knockout Allelesmentioning
confidence: 99%